O sobrenatural na fantasia vampiresca de André Vianco - Silva, Cristina Azevedo da (2015)
Fantastic literature has become, especially in the last decades of the twentieth century, an important topic of contemporary literature. The interest in the genres that integrate it is increasing, both from worldwide researchers and from readers, as can be seen by the expressive number of publications and sales of works that explore its characteristic themes: the supernatural. Currently, in the Brazilian scene, a writer in the fantasy genre that has stood out is Andre Vianco. His works tell stories that usually involve vampires characters. Aiming to investigate and analyze how to build the supernatural in the narrative of O Vampiro rei, from André Vianco, we opted for a descriptive, qualitative and bibliographic research. How essential theoretical basis for this research highlight: the features and particularities of genres fantastic, strange and wonderful that integrate fantastic literature (TODOROV, 1975; FURTADO, 1980), the construction of the characters (CANDIDO; ROSENFELD, 1976), as well as the levels of narrative structure (BARTHES, 2013; TODOROV, 2013). By analyzing out the elements inherent in fiction prose, present the particularities of the narrative and the construction of the characters through elements of the fantastic and of the wonderful genres, also bringing the psychological aspect of the characters that contributes, as well as other elements to constitute the overall meaning of the text